Nonlinear Interaction Between the Drivers of the Monsoon and Summertime Stationary Waves. Issue 14 (19th July 2021) - Garfinkel, Chaim I.; White, Ian P.; Gerber, Edwin P.; Adam, Ori; Jucker, Martin
Abstract: A moist General Circulation Model is used to investigate the forcing of the Asian monsoon and the associated upper level anticyclone by land‐sea contrast, net horizontal oceanic heat transport, and topography. The monsoonal pattern is not simply the linear additive sum of the response to each forcing; only when all three forcings are included simultaneously does the monsoonal circulation extend westward to India. This nonadditivity impacts the location of the upper level anticyclone, which is shifted eastward and weaker if the forcings are imposed individually. Sahelian precipitation, and also austral summer precipitation over Australia, southern Africa, and South America, are likewise stronger if all forcings are imposed simultaneously. The source of the nonlinearity can be diagnosed using gross moist stability, but appears inconsistent with the land‐sea breeze paradigm. This non‐additivity implies that the question of which forcing is most important may be ill‐posed in many regions. Plain Language Summary: Monsoons dominate the climate in many regions of the tropics and subtropics, and are characterized by rainy summer and drier winter seasons. This rainfall is crucial for agriculture, among other societal implications, in heavily populated regions of the world. The processes leading to regional confinement of the monsoons are investigated using an intermediate complexity moist General Circulation Model. We find that a linear perspective cannot account for the monsoons; only when land‐sea contrast, orography, and ocean heat transport are included simultaneously does the monsoonal circulation extend westward to India. A similar nonlinearity is evident for Sahelian precipitation, and also for austral summer precipitation over Australia, southern Africa, and South America. Key Points: Monsoons are due to a non‐additive response to three forcings: land‐sea contrast, orography, and ocean heat transport The non‐additivity in precipitation leads to a non‐additive response of the upper level stationary waves and Asian monsoon anticyclone Gross moist stability can account for this effect, but not the land‐sea breeze paradigm